Current Practices in the Pathologic Assessment of Breast Tissue in Transmasculine Chest Surgery. Issue 3 (24th June 2022) - Goodwin, Isak A.; Luo, Jessica; Magno-Pardon, David A.; Veith, Jacob; Willcockson, James; Carter, Gentry; Matsen, Cindy; Kwok, Alvin C.; Agarwal, Cori A.
Abstract : Background: No guidelines exist regarding management of breast tissue for transmasculine and gender-nonconforming individuals. This study aims to investigate the experiences and practices regarding perioperative breast cancer risk management among the American Society of Plastic Surgeons members performing chest masculinization surgery. Methods: An anonymous, online, 19-question survey was sent to 2517 U.S.-based American Society of Plastic Surgeons members in October of 2019. Results: A total of 69 responses were analyzed. High-volume surgeons were more likely from academic centers (OR, 4.88; 95 percent CI, 1.67 to 15.22; p = 0.005). Age older than 40 years [ n = 59 (85.5 percent)] and family history of breast cancer in first-degree relatives [ n = 47 (68.1 percent)] or family with a diagnosis before age 40 [ n = 49 (71.0 percent)] were the most common indications for preoperative imaging. Nineteen of the respondents (27.5 percent) routinely excise all macroscopic breast tissue, with 21 (30.4 percent) routinely leaving breast tissue. Fifty-one respondents (73.9 percent) routinely send specimens for pathologic analysis. There was no significant correlation between surgical volume or type of practice and odds of sending specimens for pathologic analysis. High patient costs and patient reluctance [ n = 27 (39.1 percent) and n = 24 (35.3 percent), respectively] were the most often cited barriers for sending specimens for pathologic analysis. Six respondents (8.7 percent) have found malignant or premalignant lesions in masculinizing breast specimens. Conclusions: Large variation was found among surgeons' perioperative management of chest masculinizing surgery patients regarding preoperative cancer screening, pathologic assessment of resected tissue, and postoperative cancer surveillance. Standardization of care and further studies are needed to document risk, incidence, and prevalence of breast cancer in the transmasculine population before and after surgery.